2010
DOI: 10.1097/aco.0b013e3283404579
|View full text |Cite
|
Sign up to set email alerts
|

Administration and monitoring of intravenous anesthetics

Abstract: Anesthetic drug administration might be optimized by applying knowledge from clinical pharmacokinetics and dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…1), when administered in combination. 1,2 Anaesthetists routinely combine drugs such as opioids and hypnotics in clinical practice. However, dosing is often based on building experience throughout years of training and local habits.…”
mentioning
confidence: 99%
“…1), when administered in combination. 1,2 Anaesthetists routinely combine drugs such as opioids and hypnotics in clinical practice. However, dosing is often based on building experience throughout years of training and local habits.…”
mentioning
confidence: 99%
“…TCI is a novel, individualized anesthesia method (Sahinovic et al, 2010). The results of this study showed that the MAP and HR values were stably maintained in both groups during the operation, although the values at the time of loss of consciousness were lower than those upon entering the operating room during the perioperative period.…”
Section: Discussionmentioning
confidence: 80%
“…The Paedfuser model was especially developed for children and tested in children aged 1-18 years and 5-61 kg body weight. It is recommended and accurate in patients aged 3-16 years and 15-61 kg body weight [46][47][48][49][50][51][52].…”
Section: Total Intravenous Anesthesia and Target-controlled Infusionmentioning
confidence: 98%
“…The first model developed was the Diprifusor [45,46]. After its patent expired, other models were developed like the Marsh model [46][47][48][49][50][51], the Schnider model [46][47][48][49][50][51], the Kataria model with the Katfuser [46,51], the Paedfuser model for children [52], and the White model [53,54 & ]. The above-mentioned open TCI systems can be programmed with any pharmacokinetic model and allow either plasma-site-targeting or effect-site-targeting.…”
Section: Total Intravenous Anesthesia and Target-controlled Infusionmentioning
confidence: 99%